AN ANALYSIS OF ENGLISH WORD FORMATION PROCESSES IN BEATS APART NOVEL BY ALANDA KARIZA AND KEVIN ADITYA - Riryn Fatmawaty; Putri Ayu Anggraini (E-LINK JOURNAL, 2019)
This research discusses word formation process used in Beats Aparts novel By Alanda Kariza And Kevin Aditya. The aims to describe how are English word created and found out types of word formation processes. To analyze the data found the researchers applied English word formation in English morphology.This is qualitative descriptive research. The data were taken from Beats A parts novel By Alanda Kariza And Kevin Aditya. The main theory which was used in this  research is taken from the book under the titleThe Study of Language,Third Edition byYule (2006). The result of this research showed that the process of borrowing from other language, there were Spain, China, French, Italy and Germany. The process of compounding, found out some category, there wereAdv + N, Adv + Adv, Adv + Adj, Adv + V, Adj + N, Adj + Adv, Adj + V, V + N, V + Adj, N + N, N + Adv, N + Adj, N + V. The process of clipping found out two category, there are foreclipped and backclipped. The process of conversion only found word from noun became adverb. The process of derivation consist from adding prefix such us un-, re-, dis-, im-. Adding suffix such us –ly, -ish, -er, -ness, -ion / tion, -able,  -ful, -ship, -ment, -ate, -r, -en, -ity, -tic, -ism, -al, -ar. Adding infix such us –s-, -ly-, -bor-. The process of multiple processes is all words including multiple processes in this research have a word that covers the processes of back formation and derivation. This research found out types of English word formation processes such as borrowing, compounding, blending, clipping, back formation, conversion, acronyms,derivation and multiple processes. The researcher hopes that this research can improve the knowledge about morphology, especially in word formation. Key words: Morphology, Word formation, Novel